Socioeconomic deprivation and patient-reported outcomes in symptom management trials for patients with breast cancer. Issue 28 (1st October 2022) - Vaidya, Riha; Till, Cathee; Henry, Norah Lynn; Fisch, Michael Jordan; Hershman, Dawn L.; Unger, Joseph M.
Abstract : 158 Background: Patient-reported outcomes (PROs) provide important metrics to guide treatment decision making and have been shown to be predictive of clinical outcomes. Neighborhood socioeconomic deprivation, characterized by lower levels of income, education, and housing quality, has been shown to be associated with worse outcomes in clinical trials. However, the relationship between deprivation and PROs in clinical trials has not been systematically examined. Methods: We examined the relationship between multiple PRO domains and deprivation using data from 3 randomized trials (S0927, S1200, S1202) of interventions for aromatase inhibitor (AI)-associated musculoskeletal symptoms (AIMSS) among female breast cancer patients. The studies were conducted by the SWOG Cancer Research Network. Deprivation was measured using patients' residential zip code linked to the area deprivation index (ADI), measured on a 0-100 scale and categorized into tertiles based on national ADI distribution. Multivariable linear regression was used with adjustment for patient age, race, ethnicity, cancer stage, days on AI, and body mass index (BMI). Secondary models adjusted for rurality and insurance (Medicaid/no insurance v. private/Medicare). Average joint pain and pain interference (each on 0-10 scales) based on the Brief Pain Inventory, and physical and functional wellbeing (PWB, FWB) based on the FACT-ES (on 0-28 scales), at baseline were analyzed. Results: Overall, 761 patients were examined. Median age was 60 years, 8% of patients were Black, 5.5% were Hispanic, 87% had Stage I or II disease, and median duration on AI was 365 days. 51% of patients were from least deprived areas (bottom tertile of ADI), while 15% were from the most deprived areas (top tertile). Compared with patients from the least deprived areas, patients in the most deprived areas had worse FWB (β = -1.53, 95% CI: -2.7, -0.4; p =.01) and average pain scores (β = 0.51, 95% CI: 02, 0.8; p = 0.002) at baseline. Patients from more deprived areas (middle tertile of ADI) had worse FWB (β = -1.3, 95% CI: -2.1, -0.4; p =.005) and pain interference (β = 0.5, 95% CI: 0.2, 0.9; p =.002) compared to those from least deprived areas. For pain outcomes, the ADI coefficient was attenuated but statistically significant with adjustment for insurance. The association of FWB with ADI was not statistically significant after adjusting for insurance. No statistically significant differences were noted for PWB. Conclusions: Patients with AIMSS who live in neighborhoods with higher social needs had slightly worse FWB joint pain, and pain interference at baseline, but similar PWB. The effect of insurance on the PRO-ADI association indicates that individual access to healthcare explains some of the area-level differences in PROs. Future work will examine differences in PRO trajectory by ADI, adjusted for insurance, over the course of patient participation in these trials.